The Effect of The Effectiveness of Functions, Services and Implementation of E-SPT in The Era of The Covid-19 Pandemic on The Satisfaction of Taxpayer of Personal People in The South Tangerang Region - Tri Utami; Ridho Mukson, Rozan (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2022)
Abstract Purpose: This study aims to examine and analyze the effect of effectiveness of the E-SPT function, Tax Services and the Application of E-SPT on the satisfaction of individual taxpayers. Methodology: In this study, the data used to measure the effect of Functional E-SPT, Tax Services and Application of E-SPT on Individual Taxpayers Satisfaction by distributing questionnaires to Taxpayers at KPP Serpong Pratama. The number of respondents who filled out the questionnaire was 100 respondents. Findings: The results of previous tests have examined the effect of implementing e-SPT and tax services but not on the satisfaction of individual taxpayers. Here, the researcher wants to add a function variable, tax service, and also the application of e-SPT to measure and compare with previous research. Novelty: This study continues previous research by using a different population and adding a new variable. Keywords: Effectiveness Of Functions, Services, And Implementation Of E-Spt, Satisfaction Of Taxpayer Of Personal People